PLAY THERAPY: A CONCEPTUAL ASSESSMENT OF METHODS AND TOOLS - Kahveci, Müedin; Dursun, Ayshenur (International Scientific Journal Vision, 2022)
Purpose: Play therapy; Helps to understand the emotions and what is going on in the spiritual world before educating the child and allows the child to be treated in this way. The aim of this study is to evaluate the play therapy, methods, types and tools in a conceptual framework. Thus, the advantages and disadvantages of these methods will be determined by revealing different play therapy methods and types. Method: In the play therapy, the toy played by the child is different from that at home, and each of them is subjectively chosen in the game room, creating a therapeutic effect. Descriptive method was also used in this study. Thus, play therapy will be evaluated conceptually, its methods, types and tools. The effects in the applications are expressed symbolically. Play therapy is provided to develop directly with the nature of the play that can perceive the inner world of its children. Play therapy, which aims to find ways to improve and improve the problems that children experience until today, has developed different methods and techniques against all these problems. These methods are taken as directed play therapy and non-directed play therapy as the main title. Findings: Play therapy against the unsolvable problems of children; Since it is solution oriented, it has a healing power. As a result of play therapy, it is necessary to eliminate the behavioral, emotional and psychological problems that the child feels emotionally good and affects the normal development of the child, and the growth of such problems should be prevented. Conclusion: Play therapy is a type of therapy in which children can express themselves by using games and toys. Play therapy is an appropriate range for children between the ages of 2 and 13. Play therapy sessions last from 30 to 50 minutes. In addition to the fact that the play is very useful for the child, it is also important that the child plays the game for his physical and mental health. The play therapist can talk to an adult and adolescent and do the therapy. Because the adult is aware of the problem and he can express this to the therapist without difficulty. The child can speak to an adult individually; but it can be observed that the mental capacity of the child to express himself has not been improved or is not yet as the mature’s or adult’s. In addition, play therapy helps the child to cope with difficulties, find solutions and develop problem solving skills and abilities.